Assay development for determination of tenofovir in human plasma by solid phase analytical derivatization and LC–MS/MS. (December 2015) - Podany, Anthony T; Sheldon, Curtis; Grafelman, Daryl; Ohnmacht, Corey M
Background: A novel method was developed and validated to measure tenofovir in human plasma.Results/Methodology: This method employed solid phase analytical derivatization and analysis by LC–MS/MS. Stable-labeled internal standard was added to plasma samples followed by solid phase extraction. Retained analytes were derivatized on the solid phase extraction cartridges with a diazomethane solution to yield methyl-ester derivatives. Samples were analyzed using LC–MS/MS incorporating the use of a strong cation exchange column. The method was validated over a range of 5.00–750 ng/ml. The approach developed in this report for tenofovir could be applied to other analytes that share similar structural similarities.Conclusion: The tenofovir LC–MS/MS method was used to support a clinical study of over 400 samples with a 100% success rate.